Pengaruh Leadership Position dan Financial Literacy terhadap Keputusan Investasi - P. E. Sudjiman; Lorina Siregar Sudjiman; Francis Hutabarat (Universitas Batanghari Jambi, 2023)
When the investment industry develops rapidly, the general public's demand will increase, and it is generally assumed that investing will increase one's income. One aspect of personal finance that has caught the attention of academics is the concept of investment risk. Risk takers include those with lavish lifestyles, high-level jobs, and leadership roles within companies. The main objective of this study is to better understand the impact of leadership position and financial literacy on investment decisions. Quantitative method with correlated design is used in this research. Questionnaire results data were used in this study through a sample data collection technique involving 239 individuals drawn from six communities. SPSS is an analytical tool used in research as a strategy analysis. Findings from studies on the influence of leadership and financial literacy on investment decisions suggest a measurable, if modest, impact. A person's financial literacy has no effect on investment decisions, although a person's leadership position does have some influence in this area.